Pelatihan Penyuluhan Pola Hidup Bersih Sehat dan Vaksin di Masa Pandemi Covid 19 Desa Karanglo Kecamatan Kerek Kabupaten Tuban - Novialita Angga Wiratama; Ina Agustin; Iis Daniati Fatimah (Pelita: Jurnal Pengabdian kepada Masyarakat, 2021)
Public attention to the importance of clean and healthy living behavior (PHBS) is still relatively minimal. The people of Desa Karanglo, Kecamatan Kerek Kabupaten Tuban, need counseling and training as well as assistance regarding this PHBS. This community service aims to provide knowledge and information, especially during a pandemic like today. During this COVID-19 pandemic, everyone must implement PHBS to increase body immunity and always apply the health protocol in the form of 5M. Creating a healthy life in addition to fulfilling the nutritional balance of the family requires the role of the family, especially the role of the mother in providing health awareness and supervision for family members. The purpose of this community service program is to provide PHBS training and counseling as well as to socialize the importance of vaccines in the pandemic era. Community service partners who are PKK members are expected to gain insight, awareness, willingness and ability of the community to live clean and healthy lives in the face of the COVID-19 pandemic and have awareness and implement vaccine programs from the government. This community service method uses counseling and training methods, discussions and direct practice (learning by doing). The results of community service after partners participated in activities and filled out questionnaires showed that the material provided was in accordance with what the participants needed, the ability of the training instructor to provide counseling and training was as expected, participants had high enthusiasm in community service activities. Participants have an understanding and additional insight into PHBS and vaccination. There is relevance of current conditions with the material presented.